Legal Protection of The Customary Rights of The Pubabu-Besipae Indigenous People - Bonte, Yesyurun (Jurnal Indonesia Sosial Sains, 2024)
Ulayat land is land shared by indigenous communities. Customary land is closely related and is an integral part of customary land rights. Customary rights are the rights owned by indigenous peoples to utilize natural resources for survival. The existence of indigenous communities has been explicitly recognized in national law, such as the Basic Agrarian Law and the Forestry Law. However, recognition of customary rights is still often ignored by the Government, this is the case in the Pubabu-Besipae indigenous community. Therefore, the aim of this research is to find out how the law protects the customary rights of indigenous communities. This research uses normative legal methods and uses a statutory approach. The research findings show that legal recognition and protection of customary rights are very clearly recognized and regulated, so the government should not be able to control customary land arbitrarily according to its wishes. Ownership of customary land has limitations in carrying out legal actions and must take into account the prosperity of indigenous communities. So the actions taken by the East Nusa Tenggara Government are actions that violate the human rights of indigenous peoples because there are arbitrary actions and even acts of violence against indigenous peoples. The government should hold joint discussions with indigenous communities to reach a fair agreement.